ANALYTICAL METHODS FOR QUALITY CONTROL OF NANOFORMULATIONS-A REVIEW - K, BHAVYASRI; REDDY B, ANILA; SUMAKANTH, MOGILI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
There has been a surge in enthusiasm for the creation of innovative medication modes of delivery that utilize nanoparticles in recent years. Nanoparticles provide substantial benefits compared to conventional drug delivery methods with strong stability, specificity, and drug consumption levels. The rate of release, the capacity to use alternative routes of delivery, and the capacity to give off drug compounds that are both hydrophilic and hydrophobic are all advantages. This study concentrates on nanoscale categorization, processing methods, characterization, utilization, and benefits.